2018
DOI: 10.1016/j.marenvres.2017.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for reduced mortality of Agaricia lamarcki on a mesophotic reef

Abstract: Mesophotic Coral Ecosystems (MCEs) may act as a refuge for impacted shallow reefs as some of the stressors affecting tropical reefs attenuate with depth. A less impacted population at depth could provide recruits to recolonise shallow reefs. Recently, disturbance has been reported on several mesophotic reefs including storm damage, biological invasions, and coral bleaching; calling into question the extent of deep reef refuges. We report on a reciprocal transplant experiment between shallow and mesophotic reef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…This leads us to believe that the potential adaptation of deeper colonies may not prevent connectivity between shallow and mesophotic reefs and may permit a deep-water refuge for A. lamarcki at this location. This is supported by the lack of an observed effect of depth on the cellular oxidative stress indicator DMSO:DMSP, and by no impact of collection site on the survival of the same colonies sampled here during a transplant experiment (Laverick & Rogers, 2018). A similar situation has been noted for E. paradivisa in the Red Sea (Eyal et al ., 2015).…”
Section: Discussionsupporting
confidence: 58%
“…This leads us to believe that the potential adaptation of deeper colonies may not prevent connectivity between shallow and mesophotic reefs and may permit a deep-water refuge for A. lamarcki at this location. This is supported by the lack of an observed effect of depth on the cellular oxidative stress indicator DMSO:DMSP, and by no impact of collection site on the survival of the same colonies sampled here during a transplant experiment (Laverick & Rogers, 2018). A similar situation has been noted for E. paradivisa in the Red Sea (Eyal et al ., 2015).…”
Section: Discussionsupporting
confidence: 58%
“…MCE corals have been shown to experience drastic seasonal variations in the energetic content compared to shallow corals [73]. It is generally accepted that the ecological advantages acquired by corals in their native habitat may jeopardize their survival in cases of abrupt environmental change [74]. However, for the otherwise strictly mesophotic E. paradivisa in the Red Sea, shallow waters may be advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that MCEs can be divided into two distinct zones: an upper mesophotic one, between 30-60 m; and a lower one, below 60 m (Lesser et al, 2010;Brazeau et al, 2013;Bongaerts et al, 2015). It has also been broadly suggested that deeper reefs are less affected by direct climate-induced disturbances compared to shallow reefs (Glynn, 1996;Hughes and Tanner, 2000;Bak et al, 2005;Laverick and Rogers, 2017;Baird et al, 2018) and, therefore, the occurrence of thriving MCE communities has led to the "deep-reef refuge hypothesis" (DRRH: Bongaerts et al, 2010Bongaerts et al, , 2019. It is hypothesized that MCEs may function as a refuge for certain organisms during periods of stress in the shallow waters and, in the aftermath, act as a potential source of propagules for recovery of the disturbed shallow communities (e.g., Kahng et al, 2014;Bongaerts et al, 2017).…”
Section: Introductionmentioning
confidence: 99%